(untitled) (Research, Society and Development, 2022)
Objective: To describe the application of the Systematization of Nursing Care to a multiple trauma patient victim of a traffic accident. Methodology: Descriptive study of the experience report type, carried out based on the description of the reality experienced in the application of the Systematization of Nursing Care during the care of a patient with multiple traumas hospitalized in a medium and high complexity hospital from July to August of 2020. Results: During the application of the Systematization of Nursing Care, eight nursing diagnoses were evidenced, namely: anxiety, constipation, deficit in self-care for bathing, acute pain, impaired skin integrity, risk of falling and risk of infection. Based on the diagnoses found, the necessary interventions were carried out, goals were established and, finally, the actions were evaluated. Final Considerations: The present study contributed to highlighting the importance of nurses and the use of Nursing Systematization in providing specialized care to patients in order to identify problems and carry out appropriate interventions to minimize them.